DISPARITAS PUTUSAN PIDANA TERHADAP TINDAK PIDANA NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Judicial power is a guide for judges in forming an independent judiciary. This means the power of the judiciary is free from the intervention of the parties and the power of the State unless otherwise determined by law. The freedom of the judge in passing his decision has a negative impact, namely criminal disparity. In this paper, the author focuses on the occurrence of funding disparity against the criminal decision of narcotics abuse issued by the Pekanbaru High Court. The purpose of writing this thesis: First, to know the judge’s perspective in deciding the decision of the appellate court on narcotics crime cases under Law Number 35 of 2009 on Narcotics. Second, to know the negative impact that arises from the disparity of punishment on law enforcement of narcotics crime. Third, to know the right conviction idea to solve the problem of narcotics trafficking in Indonesia. The author conducts this research with normative research methods or library studies in order to obtain secondary data obtained from documentary studies that is by studying and analyzing descriptively comparatively to the legislation with theories related to the problems studied. From the result of the study there are three main things that can be concluded: First, the Pekanbaru High Court’s Judge has different perspectives in making decisions, thus causing disparity of punishment. Second, the negative impact from this disparity of punishment is the emergence of social jealousy and negative views by the defendant, the community and the community that have potential to commit a narcotics crime against judicial institutions. Third, the right conviction idea to solve the problem of narcotics trafficking in Indonesia can be done by establishing the idea of a “Double Track System” punishment. The author's advice, the panel of judges in imposing criminal sanction must be based on consideration that have truly provided a sense of justice to each party and the need for a guiding instrument for the administration of crimes in criminal law in Indonesia.Keywords: Disparity – Judgement – Narcotics Crime